Improving Credit Risk Assessment in MSMEs: A Machine Learning-Based Approach - Mishra, Megha; Varshney, Manish (International Journal of Computer Sciences and Engineering, 2023)
This paper delves into the utilization of machine learning (ML) to enhance the credit risk assessment of Micro, Small and Medium Enterprises (MSMEs). With the burgeoning digital economy and growing complexities in financial transactions, traditional methods for assessing credit risk are proving inadequate. The research aims to establish an ML model that will offer more accurate, reliable, and efficient credit risk assessment in the MSME sector. The model’s development, implementation, and performance are critically evaluated using real credit data from various banks.